Characteristics of joint torques in performing the basket to handstand on parallel bars - Yamada, T.; Sato, Y. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
The purpose of this study was to investigate characteristics of joint torques in performing the basket to handstand on parallel bars. Twenty-six male elite gymnasts were videotaped in the national championships. Two-dimensional motion analysis technique and inverse dynamics approach were used for calculating the kinematic and kinetic parameters. The shoulder and hip joint torques did not relate to the upward velocity, but significantly related to the downward and forward velocities in performing the basket to handstand. Development of the shoulder flexion torque should be as small as possible for the execution to use the greater swing velocity.